2013
DOI: 10.1371/journal.pone.0073607
|View full text |Cite
|
Sign up to set email alerts
|

IMD-0354 Targets Breast Cancer Stem Cells: A Novel Approach for an Adjuvant to Chemotherapy to Prevent Multidrug Resistance in a Murine Model

Abstract: Although early detection of breast cancer improved in recent years, prognosis of patients with late stage breast cancer remains poor, mostly due to development of multidrug resistance (MDR) followed by tumor recurrence. Cancer stem cells (CSCs), with higher drug efflux capability and other stem cell-like properties, are concentrated in a side population (SP) of cells, which were proposed to be responsible for MDR and tumor repopulation that cause patients to succumb to breast cancer. Therefore, targeting of CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…Both TAAs are highly expressed in the lung metastases and tumor of the 4T1 model. 26 As shown in Figure 3A, B, the production of IFNg by spleen cells restimulated with both TAAs Mage-b and Survivin of mice receiving cryoablation and Meriva, was significantly higher compared to all control groups. In addition, depletion of CD8 C T cells in the spleen cultures of mice receiving cryoablation and Meriva resulted in a significant reduction in the number of IFNg-producing spleen cells compared to non-CD8…”
Section: The Effect Of Cryoablation Plus Meriva On T Cell Responses Tmentioning
confidence: 79%
“…Both TAAs are highly expressed in the lung metastases and tumor of the 4T1 model. 26 As shown in Figure 3A, B, the production of IFNg by spleen cells restimulated with both TAAs Mage-b and Survivin of mice receiving cryoablation and Meriva, was significantly higher compared to all control groups. In addition, depletion of CD8 C T cells in the spleen cultures of mice receiving cryoablation and Meriva resulted in a significant reduction in the number of IFNg-producing spleen cells compared to non-CD8…”
Section: The Effect Of Cryoablation Plus Meriva On T Cell Responses Tmentioning
confidence: 79%
“…C T-cell responses to TAAs Mage-b and Survivin, both highly expressed by 4T1 tumor cells, 8,9 were observed in the spleens of mice treated with 1 high and multiple low doses of c-di-GMP. Also, this combination resulted in a near elimination of all metastases and a significant decrease in tumor growth.…”
Section: Multiple Pathways Of C-di-gmp In Cancer Immunotherapymentioning
confidence: 99%
“…For example, engineered exosomes loaded with doxorubicin can be safely delivered to the tumor microenvironment, demonstrating similar tumor growth inhibition with less adverse effects compared with equipotent free drug (56)(57)(58) (60) demonstrated that exosomes loaded with HGF siRNA could inhibit tumor growth and angiogenesis in gastric cancer. It is hoped that an exosome-based approach for the treatment of gastric cancer with or without peritoneal dissemination will be developed in the near future.…”
Section: Chemoresistance and Exosome-based Treatment Of Peritoneal DImentioning
confidence: 99%